Preventable multiple high-risk birth behaviour and infant survival in Nigeria - Mobolaji Modinat Salawu; Rotimi Felix Afolabi; Babatunde Makinde Gbadebo; Adetokunbo Taophic Salawu; Adeniyi Francis Fagbamigbe; Ayo Stephen Adebowale (BMC, 2021)
Abstract Background Globally, infant mortality has declined considerably but has remained unacceptably high in sub-Saharan Africa, especially Nigeria where infant mortality rate is 67/1000 live births. To facilitate infant mortality reduction in Nigeria, an understanding of the synergistic effect of bio-demographic characteristics of mothers known as High Risk Birth Behaviours (HrBBs) is important. We therefore investigated the influence of HrBBs on infant survival in Nigeria. Methods This cross-sectional study design utilized data from the 2018 round of Nigerian Demographic Health Survey. The study participants were a representative sample of women of reproductive age (n = 21,350) who had given birth within the 5 years preceding the survey. HrBBs was measured through integration of information on maternal age at child's birth, parity, and preceding birth interval with respect to the most recent child. The HrBBs was categorized as none, single and multiple. Data were analysed using descriptive statistics, Log-rank test and Cox proportional hazard model (α =0.05). Results The mean age of the women was 29.7 ± 7.2 and 4.1% had experienced infant death. Infant mortality was highest among women with multiple HrBBs (5.1%). Being a male, having small size at birth, failure to receive tetanus injection, non-use of contraceptives and living in the core-north (North West and North East) predisposed children to higher risk of dying before 12 months of age. The hazard ratio of infant mortality was significantly higher among infants of mothers in multiple HrBBs category (aHR = 1.66; CI: 1.33-2.06) compared to their counterparts with no HrBBs. Conclusion Multiple HrBBs increase the chances of dying among infants in Nigeria. Screening women for HrBBs for special health attention during pregnancy, birth and postnatal period will alleviate infant death in Nigeria.